Estimating the Effect of Contrast Exercises Using Conventional Deadlifts and Air Rower on Increasing Leg Muscle Strength and VO₂max in Rowing Athletes - Nurkholis; Dwi Cahyo Kartiko; Irmantara Subagio; Andri Suyoko; Adi Pranoto (OVS LLC, 2024)
Objectives. This study aimed to prove the effect of contrast training using conventional deadlifts and air rowers on the increase of leg muscle strength and VO₂max in rowing athletes. Materials and methods. This study used a true-experimental method with a two-group pretest-posttest approach, involving a control group design. A total of 22 rowing athletes, aged 19-23 years, and recruited from the Surabaya City training centre, were involved in the study. The athletes received a contrast training intervention with a high intensity of 85-90 % 1RM, conducted thrice per week for a six-week period. Leg strength and back strength, leg power, and VO₂max were evaluated between pre- and post-intervention in each study group. Results. The results showed that leg strength and back strength, leg power, and VO₂max were found to be significantly improved after performing a contrast exercise intervention compared to the control group (p ≤ 0.05). Conclusions. These findings suggest that contrast training combining conventional deadlifts and air rowers is an effective method of increasing leg muscle strength and power, as well as VO₂max in rowing athletes, so that it can provide benefits to enhance the explosive strength and aerobic endurance of these athletes.